Integrated strategies enhance soil fertility restoration effectiveness in ion-adsorption rare earth mining areas: A meta-analysis - Tao Wang; Yizhen Liu; Jun Ye; Sheng Xu; Qiying Cai; Yongxiu Li; Lan Wu; Chi Yao; Gang Ge (Global Ecology and Conservation)
The extraction of ionic rare earth elements has resulted in significant land degradation, with low soil fertility posing a critical challenge to ecological restoration in these regions. Despite extensive efforts, the effectiveness of soil fertility restoration measures remains debated, and the success of these interventions is not yet fully established. This study employs a meta-analysis to evaluate the effects of soil fertility restoration measures in ionic rare earth mines and to assess the influence of technical details on restoration outcomes. Although soil fertility has generally improved following restoration efforts, it remains at a relatively low level, with a potential risk of diminishing effectiveness over time. Single restoration measures exhibit substantial limitations, underscoring the necessity of an integrated restoration strategy in severely degraded ionic rare earth mines. Within this integrated restoration framework, factors such as the type and dosage of soil conditioners, microbial inoculation, and species selection and configuration play pivotal roles in determining restoration success. A phased species configuration strategy within this framework may yield more effective and sustainable restoration outcomes. Despite certain limitations, these findings offer valuable insights for optimizing soil fertility restoration practices in severely degraded ecosystems, advancing scientific understanding, and providing practical recommendations for enhancing the long-term sustainability of restoration efforts.